2022
DOI: 10.1111/jen.12989
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and invasion risk assessment of Oryctes rhinoceros (L.) in China under changing climate

Abstract: Biological invasion is one of the greatest threats to agriculture, human health and the global economy. Palm crop is a precious large evergreen arbour mainly growing in tropical areas. Its main habitats are in provinces of Hainan,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The previous literature confirms that the extent of the distribution of C. viridis is associated with the extent of the plant distribution area affected, while that the scope of activity can be influenced by various factors, though this scope is limited to the habitat [47,48]. There are notable differences between various periods and climate change situations, which might be connected to variations in temperature and rainfall in various emission scenarios [16]. According to Figure 4, over time, the trend of highly suitable areas will gradually rise; the suitable area will expand to the south and continue to increase in areas such as Hubei, Anhui, Jiangsu, and Hainan.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The previous literature confirms that the extent of the distribution of C. viridis is associated with the extent of the plant distribution area affected, while that the scope of activity can be influenced by various factors, though this scope is limited to the habitat [47,48]. There are notable differences between various periods and climate change situations, which might be connected to variations in temperature and rainfall in various emission scenarios [16]. According to Figure 4, over time, the trend of highly suitable areas will gradually rise; the suitable area will expand to the south and continue to increase in areas such as Hubei, Anhui, Jiangsu, and Hainan.…”
Section: Discussionmentioning
confidence: 74%
“…There have been numerous studies indicating that this model demonstrates superior performance in terms of predictive accuracy, especially when species distribution data are lacking. It is one of the most accurate approaches for estimating a species' probable geographic range, and it is more accurate than existing alternative models [16]. As a result of their quick running times, ease of operation, low sample demand, and stable outcomes [17,18], models of species distribution have been extensively used to forecast the spread of invasive species [19,20], the potential geographic distribution of endangered plants [13,21], changes in wild animal habitats [22], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, minimum temperature of coldest month, followed by precipitation of wettest month were reported by Hao et al 57 as the main drivers of the global distribution of O. rhinoceros based on BRT model. Xu et al 71 reported that the precipitation of the wettest month was the most important driver of the potential distribution of O. rhinoceros . The variation in the modeling results could be associated with the modeling technique, environmental variables and the number of O. rhinoceros distribution points.…”
Section: Discussionmentioning
confidence: 99%
“…Rainfall plays a crucial role in the growth and reproduction of insects by affecting the humidity of their environment (Xu et al, 2022).…”
Section: Ta B L Ementioning
confidence: 99%